Term pregnancy after minimally invasive surgical treatment of Herlyn-Werner-Wunderlich syndrome - Mirković Ljiljana; Ljubić Aleksandar; Janjić Tijana; Milićević Srboljub; Sparić Radmila; Jeremić Katarina; Pantović Sveto; Milenković Vera (Srpski Arhiv za Celokupno Lekarstvo, 2013)
Introduction. Uterus didelphys with obstructed hemivagina and ipsilateral renal agenesis represents a complex congenital anomaly, also known in the literature as Herlyn-Werner-Wunderlich (HWW) syndrome. Case Outline. A 16yearold patient presented with secondary amenorrhoea and abdominal pain. Her history revealed anorexia nervosa; she had menarche at the age of 14; her menstrual cycles were regular, with progressive dysmenorrhoea. Nine months after the explorative laparotomy performed at the regional healthcare center there was no a definitive diagnosis. Pelvic examination showed a paravaginal pelvic mass located on the right side. Magnetic resonance imaging of the abdomen and pelvis confirmed the diagnosis of HWW syndrome. Transvaginal excision and marsupialisation of the vaginal septum were performed. Regular menstrual cycles were resumed after four years following the treatment of anorexia nervosa. Twelve years after the operation, the patient conceived spontaneously; pregnancy developed in the left nonobstructed uterus. She underwent Cesarean section at the 37th gestational week and gave birth to a healthy female infant. Conclusion. HWW syndrome is an uncommon cause of abdominal pain and progressive menstrual discomfort shortly after menarche. It is therefore essential to maintain a high index of suspicion of the existence of this syndrome in such cases, since prompt and adequate treatment prevents the development of complications and allows for preservation of the reproductive potential of both hemiuteri. [Projekat Ministarstva nauke Republike Srbije: Celularni i molekularni patogenetski mehanizmi poremećaja reprodukcije i genitalnih organa u prevenciji, dijagnostici i terapiji podprojekat, br. 41021: Tretmani antenatalnih hidronefroza]